2011
DOI: 10.1002/ijc.26284
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of prostate‐derived Ets factor by luteolin causes inhibition of cell proliferation and cell invasion in prostate carcinoma cells

Abstract: Luteolin is a polyphenolic flavone and has antitumor activity for many cancers. The prostate-derived Ets factor (PDEF), a novel epithelium-specific Ets transcription factor, acts as an androgen-independent transcriptional activator of the prostate-specific antigen (PSA) promoter. We determined the antitumor function of luteolin via upregulation of PDEF gene expression in human prostate carcinoma LNCaP cells. Results from flow cytometry and Prostate derived Ets transcription factor (PDEF), a novel epithelium-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 45 publications
2
46
0
1
Order By: Relevance
“…The GDF15 primers (5 0 -GGCCAACCAGAGCTGG-GAAG-3 0 and 5 0 -GCCCGAGAGATACGCAGGT G-3 0 ) were used to amplify sequences specific to human GDF15 mRNA. The sequence of primers used to amplify sequences specific to human maspin, N-myc downstream-regulated gene 1 (NDRG1), matriptase, IL6, and b-actin were previously described (Tsui et al 2008a(Tsui et al , 2011b(Tsui et al , 2012a. After separation by 2% agarose gel electrophoresis, the PCR products were visualized by ethidium bromide staining.…”
Section: Semiquantitative and Real-time Rt-pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…The GDF15 primers (5 0 -GGCCAACCAGAGCTGG-GAAG-3 0 and 5 0 -GCCCGAGAGATACGCAGGT G-3 0 ) were used to amplify sequences specific to human GDF15 mRNA. The sequence of primers used to amplify sequences specific to human maspin, N-myc downstream-regulated gene 1 (NDRG1), matriptase, IL6, and b-actin were previously described (Tsui et al 2008a(Tsui et al , 2011b(Tsui et al , 2012a. After separation by 2% agarose gel electrophoresis, the PCR products were visualized by ethidium bromide staining.…”
Section: Semiquantitative and Real-time Rt-pcrmentioning
confidence: 99%
“…Equal quantities of cell extract were loaded onto a 10% SDS-polyacrylamide gel and analyzed using the Western lightning plus-ECL detection system (PerkinElmer, Inc., Waltham, MA, USA) as described previously (Tsui et al 2012a). The blotting membranes were probed with 1:5000 diluted polyclonal matriptase antiserum (IM1014; Calbiochem, Darmstadt, Germany), 1:1000 diluted maspin antiserum (554292; BD Biosciences, Bedford, MA, USA), 1:5000 diluted NDRG1 antiserum (N-19; Santa Cruz Biotechnology), 1:500 diluted GDF15 antiserum (07-217; Upstate Biotechnology, Charlottesville, VA, USA), or 1:1000 diluted antib-actin antiserum (C11, Santa Cruz Biotechnology).…”
Section: Immunoblot Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids are principally categorized into flavones, flavonols, flavanols, flavanones, flavanonols and isoflavones (13,14). Genistein (isoflavone), luteolin (flavone) and quercetin (flavonol) are typically present in numerous fruits and vegetables, and have been shown to inhibit cell proliferation with variable efficacy in human prostate cancer (15)(16)(17). Consistent with these findings, the present study observed that genistein, luteolin and quercetin inhibited the proliferation of prostate cancer cells in a dose-dependent manner and in the following order of potency: Genistein>luteolin>quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…The prostate-derived ETS factor (PDEF) is limited to tissues that are of epithelial origin and are hormone-regulated, such as prostate, breast, salivary glands, ovaries, colon, airways and stomach tissues (7,(10)(11)(12)(13)(14)(15). In the prostate, PDEF is predominantly expressed in the luminal epithelium, acting as an activator of the transcription of prostate-specific antigen (PSA), either in the androgen-sensitive or androgen-independent setting (16)(17)(18). ETS variant 4 (ETV4) may be involved in chromosomal translocations in human Relative mRNA expression of prostate-derived E-twenty-six factor and E-twenty-six variant 4 transcription factors, and of uridine phosphorylase-1 and thymidine phosphorylase enzymes, in benign and malignant prostatic tissue LUCIANE ROSTIROLA CAVAZZOLA 1* , GUSTAVO FRANCO CARVALHAL 2* , CANDIDA DEVES 1 ,…”
Section: Introductionmentioning
confidence: 99%